Discovery of the Potential Novel Pharmacodynamic Substances From Zhi-Zi-Hou-Po Decoction Based on the Concept of Co-Decoction Reaction and Analysis Strategy - Feng, Xin; Bi, Yuelin; Wang, Jiaqi; Li, Tianyi; Yu, Gengyuan; Zhang, Tonghua; Xu, Haoran; Zhang, Chenning; Sun, Yikun (Frontiers in Pharmacology, 2022)
Background: Zhi-Zi-Hou-Po Decoction (ZZHPD), a classic traditional Chinese medicine formula, is clinically used to treat anxiety and insomnia. The analysis strategy based on the concept of co-decoction of traditional Chinese medicine (TCM) is helpful to analyse the effective substances of traditional Chinese medicine formula in depth. Aim of the study: This manuscript intends to take ZZHPD as a model sample to explore the phenomenon of co-decoction of complex formula in the combination of Liquid chromatography-mass spectrometry (LC-MS) technology, data analysis, and molecular docking. Materials and methods: In the current research, an innovative LC-MS method has been established to study the active ingredients in ZZHPD, and to identify the ingredients absorbed into the blood and brain tissues of mice. And molecular docking studies were performed for the known compounds of the brain tissue to analyse their binding affinities. Results: Based on new processing methods and analysis strategies, 106 chemical components were identified in ZZHPD, including 29 blood components and 18 brain components. Then, by comparing the different compounds in the co-decoction and single decoction process, it was surprisingly found that 125 new ingredients were produced during the co-decocting, 2 of which were absorbed into the blood and 1 of which was absorbed into brain tissue. Ultimately, docking studies showed that the18 components of the brain tissue from ZZHPD have excellent levels of binding proteins of GABA, serotonin and melatonin receptors. The docking results of GABRA1 with naringenin and hesperidin, HCRTR1 with naringenin-7-O-glucoside, poncirenin and genipin 1-gentiobioside, and luteolin with SLC6A4, GLO1, MAOB and MTNR1A may clarify the mechanism of action of ZZHPD in treating depression and insomnia. Conclusions: Our study may provide new ideas for further exploring the effective substances in ZZHPD.